If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(1 + -6x) + 6 = -10 (1 * 2 + -6x * 2) + 6 = -10 (2 + -12x) + 6 = -10 Reorder the terms: 2 + 6 + -12x = -10 Combine like terms: 2 + 6 = 8 8 + -12x = -10 Solving 8 + -12x = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -12x = -10 + -8 Combine like terms: 8 + -8 = 0 0 + -12x = -10 + -8 -12x = -10 + -8 Combine like terms: -10 + -8 = -18 -12x = -18 Divide each side by '-12'. x = 1.5 Simplifying x = 1.5
| 6+10v=256 | | -14+10=m-10 | | 0=-6b-5b | | .6*k+5=7 | | 3x^2-14x-2=0 | | -3x+9=-6y | | -7x-9(-3)=63 | | x-9=-7+5 | | 4n-n=-12 | | x-9/3=5 | | x^4-5x^2-50=0 | | 3-5(2x-1)+1x=-10 | | 7(7y+2)-9=-2 | | -5y-9=-y+1 | | 6(c+4c)=4c-18 | | 6x+4(4x-15)=50 | | -2=w/5 | | 3k-9=7+2k-k | | -4x+4(2x+8)=-8+8(x+8) | | L+50=1.32 | | -8/9(9+y)=64 | | 5/3x+1/3x=8/3+8/3x | | -8(t-7)-7(2t+1)=-17 | | 7(x-4)=6(x+1)-3 | | 5(40-(40-x))+10(40-x)+25x=405 | | -59=-5(4a-4)+1 | | -x-(13+4x)=-3(5-9k)+2 | | -0.8(2x-6)=1.7(3-x) | | 3y+(-11y)= | | 12x^2-81x-3/7=0 | | x/3-9=11 | | 12x^2-81x-3/7 |